The linkage between motivational mechanisms, meaningful work and teachers’ innovative behaviour in public secondary schools in Northeast, Nigeria - Abubakar Bawuro, Faiza (2020)
The significance of innovative behaviour in organisations has been widely recognised in various role performances. Despite the importance of motivation to stimulate individual innovative behaviour, little is known regarding the effect of multiple motivational mechanisms in fostering innovative behaviour in a single study, especially in the education system. Also, the role of perceived meaningful work is highly essential in the work environment. However, the link between motivational mechanisms, meaningful work and individual innovative behaviour is not particularly clear. Building on the principles of job characteristics model, a proposed research model was tested by linking motivational mechanisms to teachers’ innovative behaviour. Also, the mediating role of meaningful work in their relationships was examined. Accordingly, ten hypotheses were then formulated and tested in the survey using the data collected from the 309 participants selected through a quota sampling. The study covered the Northeast region of Nigeria, which comprised six states. SPSS and SmartPLS software were used as statistical tools for data analysis. The findings revealed that two out of the three motivational mechanisms (i.e. creative self-efficacy and prosocial motivation) had a significant direct effects on teachers’ innovative behaviour than intrinsic motivation. Also, the mediation analysis found that meaningful work mediated the linkage between all the three motivational mechanisms and teachers’ innovative behaviour. For practical implications, this study suggests that school administrators should provide a well defined tasks where teachers can attach meaning and significance to their jobs. This would lead to those high in internal work motivation to engage in innovation processes. Also, there is a need for revision of teachers’ assessment to incorporate innovative behaviour criteria. The results further highlight several pathways for further study and theory advancement.